ANALISIS PRODUKTIVITAS KERJA KARYAWAN PADA PTPN VII AFDILING KALIANDA LAMPUNG SELATAN - Yohannes P Kumagaya (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
High work productivity of employees is needed in every organization in efforts to achieve thegoal. In other side, if employees’ work productivity is low, it will be difficult to achieve good results.Great attention to employees will encourage motivation and work attitude which embodies high andvery influential in the formation of employee work productivity.Wages mean everything received byemployees as remuneration for the work that has been done .Compensation received by an employee can be in natura ( cash money ) or innatura , suchas housing , meals, groceries , clothing , vehicles and other various facilities, as long as they are freein exchange for the work the employee has done .The result of the data analysis concluded that there is a significance influence of employees' wagestowards work productivity of AfdilingKalianda PTPN VII employees . The value of the coefficient ofmultiple determination is 0.565 , which means 56.5 % of work productivity of PTPN VIIAfdilingKalianda employees was influenced by wages variable .